Autocomposição na improbidade administrativa: acordo de não persecução civil e composição do litígio - Lopes, Marcela Rodrigues Pavesi (2024)
The purpose of this paper is to study the forms of self-composition applicable to administrative improbity conflicts, using as a model the proposal of two methods of selfcomposition involving the protection of the public interest proposed in the doctrine of Cláudio Madureira. To this end, the state of the art of administrative improbity is discussed, in order to delimit its jurisdiction, legal nature and concept. The next step is to relate appropriate conflict resolution methods to the principle of access to justice, establishing the premise that the Brazilian procedural model favors the use of appropriate methods for all branches of law. The history of consensuality in Administrative Law and in the protection of administrative improbity is also discussed, as well as the terms of the standardization of the Civil Non-Prosecution Agreement. Finally, we try to bring the modus operandi for the self-composition of the Public Treasury proposed by Cláudio Madureira closer to administrative improbity, demonstrating that the Non-Prosecution Agreement is a transaction, and that the other means, the settlement of disputes, should be applied in situations where the plaintiff is convinced that the misconduct did not occur.